Electrical Stimulation Mapping of Brain Function: A Comparison of Subdural Electrodes and Stereo-EEG - Grande, Krista M.; Ihnen, Sarah K. Z.; Arya, Ravindra (Frontiers in Human Neuroscience, 2020)
Despite technological and interpretative advances, the non-invasive modalities used for pre-surgical evaluation of patients with drug-resistant epilepsy, fail to generate a concordant anatomo-electro-clinical hypothesis for the location of seizure-onset zone, in many patients. This requires chronic monitoring with intracranial electroencephalography (EEG), which facilitates better localization of seizure-onset zone, and simultaneously allows evaluation of functional significance of cortical regions-of-interest, by electrical stimulation mapping (ESM). There are two principal modalities for intracranial EEG, namely subdural electrodes and stereotactic depth electrodes (stereo-EEG). Although ESM is considered the gold-standard for functional mapping with subdural electrodes, there have been concerns about its utility with stereo-EEG. This is mainly because subdural electrodes allow contiguous sampling of the dorsolateral convexity of cerebral hemispheres, and permit delineation of extent of eloquent functional areas on the cortical surface. Stereo-EEG, while having relatively sparse sampling on the cortical surface, offers the ability to access depth of sulci, mesial and basal surfaces of cerebral hemispheres, and deep structures such as insula, which are largely inaccessible to subdural electrodes. As stereo-EEG is increasingly becoming the preferred modality for intracranial monitoring, we find it opportune to summarize the literature for ESM with stereo-EEG in this narrative review. Emerging evidence shows that ESM for defining functional neuroanatomy is certainly feasible with stereo-EEG, but probably requires a different approach for interpretation and clinical decision making compared to ESM with subdural electrodes. We have also compared ESM with stereo-EEG and subdural electrodes, particularly for current thresholds required to evoke desired functional responses versus unwanted after-discharges. In this regard, there is preliminary evidence that ESM with stereo-EEG may be safer than ESM with subdural grids. Finally, we have highlighted important unanswered clinical and scientific questions for ESM with stereo-EEG in a hope to encourage future research and collaborative efforts.